2004
DOI: 10.1016/j.cardiores.2003.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Selective retroinfusion of GSH and cariporide attenuates myocardial ischemia–reperfusion injury in a preclinical pig model

Abstract: Timely application of GSH scavenging ROS and cariporide targeting ion imbalance provides cardioprotection to the postischemic heart, which is superior to either treatment alone. The lack of an effect of additional IB4 treatment may indicate that GSH/cariporide retroinfusion itself affects leukocyte-dependent reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Oxidative stress related to heart was evident in patients undergoing by-pass surgery, where oxidized glutathione (GSSG) accumulation was found to be negatively correlated with the functional recovery of the myocardium [ 6 ]. Currently, the ratio of oxidized glutathione (GSSG) to reduced glutathione (GSH) is used as a marker of oxidative stress, considering the fact that GSH, a tripeptide ( γ -glutamylcysteinylglycine) containing free thiol group, is one of the most important scavengers of ROS in the heart [ 7 , 8 ]. Furthermore, it can act as an antioxidant in association with glutathione peroxidase (GPx) catalyzed reaction by providing reducing equivalents and thereby helping in the reduction of lipid hydro peroxides ( Figure 1 ).…”
Section: Oxidative Stress In Cardiovascular Diseasesmentioning
confidence: 99%
“…Oxidative stress related to heart was evident in patients undergoing by-pass surgery, where oxidized glutathione (GSSG) accumulation was found to be negatively correlated with the functional recovery of the myocardium [ 6 ]. Currently, the ratio of oxidized glutathione (GSSG) to reduced glutathione (GSH) is used as a marker of oxidative stress, considering the fact that GSH, a tripeptide ( γ -glutamylcysteinylglycine) containing free thiol group, is one of the most important scavengers of ROS in the heart [ 7 , 8 ]. Furthermore, it can act as an antioxidant in association with glutathione peroxidase (GPx) catalyzed reaction by providing reducing equivalents and thereby helping in the reduction of lipid hydro peroxides ( Figure 1 ).…”
Section: Oxidative Stress In Cardiovascular Diseasesmentioning
confidence: 99%
“…Therefore, further investigation was performed with a focus on the antioxidant properties involved in the cardioprotective effects of YLSF. As an endogenous antioxidant enzyme, SOD plays an important role in protecting the cells from oxidative damage by converting O 2- into H 2 O 2 , and GSH is an important non-enzymatic antioxidant defense process required to maintain the normal redox state of cells and to counteract the deleterious effects of oxidative stress [28]. Our results showed that the significant decrease in the GSH-Px and SOD levels in the model group was enhanced by YLSF, which indicated the potential of YLSF to counteract oxidative damage and to reinforce antioxidant defenses.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous GSH supplementation in pigs significantly increases myocardial GSH content and resistance to ischemiareperfusion injury (36,49). Additionally, apoptosis and oxidative stress in isolated hearts perfused with high levels of glucose were attenuated by addition of GSH to the perfusion buffer (4).…”
Section: H773mentioning
confidence: 99%